Evaluation of the effect of waste clay from a polyol production process as a partial substitute for cement in reinforced concrete - Troconis de Rincón, Oladis; Millano, Valentina; Suarez, Wilfredo; Navarro, Luis; De Turris, Antonio; Amesty, Roque (Revista ALCONPAT, 2021)
In this work, the effect of waste clay from a polyol production process was evaluated, as a partial substitute for cement in reinforced concrete, in concentrations of 0%, 5% and 10%. The physico-mechanical characteristics of the concrete and the electrochemical properties of the steel were determined during a period of 356 days (ISO 11474), in 15x10x5 cm specimens, with two steel bars embedded in the concrete. The results indicate that the compressive strength decreased proportionally according to the clay content; increasing for 90 days of curing. However, the capillary sorption of the concrete decreased, which allowed the steel in the marine environment to maintain its passive state for longer than its blank specimen, for the w/c ratios evaluated (0.45 and 0.60).